Experimental study of hydrogen production using electrolyte nanofluids with a simulated light source. (8th February 2022) - Wei, Shihao; Hikmati, Javad; Balakin, Boris V.; Kosinski, Pawel
Abstract: In this research, we conducted water electrolysis experiments of a carbon black (CB) based sodium sulfate electrolyte using a Hoffman voltameter. The main objective was to investigate hydrogen production in such systems, as well as analyse the electrical properties and thermal properties of nanofluids. A halogen lamp, mimicking solar energy, was used as a radiation source, and a group of comparative tests were also conducted with different irradiation areas. The results showed that by using CB and light, it was possible to increase the hydrogen production rate. The optimal CB concentration was 0.1 wt %. At this concentration, the hydrogen production rate increased by 30.37% after 20 min of electrolysis. Hence, we show that using CB in electrolytes irradiated by solar energy could save the electrical energy necessary for electrolysis processes. Highlights: Successfully prepared a stabilized sodium sulfate electrolyte with carbon black nanoparticles. Hydrogen production increases with the increasing of the concentration of nanofluids then decrease. Carbon black nanoparticles have both positive and negative impacts on electrolysis. Using nanofluids can increase the efficiency of electrolysis.